Digital histories - Anderson, Ian; Tedd, Lucy A. (Program (Belfast, Norther Ireland), 2005)
This e-book is devoted to a selection of papers based on presentations given at the Association for History and Computing - UK (AHC-UK) annual conference, held in association with The Royal Historical Society's Gerald Aylmer Seminar at The National Archives in Kew, near London in late 2004. With contributions from the UK, USA and South Africa, this e-book explores repositories of various sizes with different aims and organisation and presents the views of historians on the creation and use of digital resources.